Research progress on risk factors for implantable venous access port-related infections in cancer patients (恶性肿瘤患者发生植入式静脉输液港相关感染危险因素研究进展) - LI Ting (李婷) (Association of Integrative Nursing, 2024)
The application of implantable venous access port (IVAP) in cancer patients is becoming increasingly common. The complications of the IVAP include infection, blockage, thrombosis, catheter dysfunction, etc. Poor nursing of the infusion port leads to the highest incidence of related infections, high costs, and serious consequences for patients. This paper summarized the risk factors related to the IVAP in perspectives of catheter, patient, disease and medical staff, and provided reference for clinical prevention of related complications. (植入式静脉输液港在肿瘤患者的应用越来越普遍。植入式静脉输液港常见并发症包括感染、堵管、血栓形成、导管功能障碍等, 其中因输液港护理不当造成相关感染的发生率最高。本文从导管、患者、疾病、医护方面总结归纳恶性肿瘤患者发生植入式静脉输液港相关感染的危险因素, 为临床预防相关并发症提供参考。)